HUBUNGAN DISMENORE DENGAN AKTIVITAS BELAJAR MAHASISWI DI STIKes IMC BINTARO TANGERANG SELATAN 2019 - Riswahyuni Widhawati; Sisca Putri Utami (STIKes IMC Bintaro, 2019)
Painful menstruation (dysmenorrhea) is a State where a great pain arises at the time of menstruation. One of the activities that can be interrupted because of painful menstruation (dysmenorrhea) is a learning activity. Dysmenorrhea is often experienced by young women in productive age. Research has shown that Dysmenorrhea can be menurukan academic achievement, learning activities, learning and social activity concentration due to menstrual pain that is felt. The research aims to know the relationship of dysmenorrhea with learning activities mahasiswi (women of fertile age) in the IMC STIKes Bintaro. This research using the method of quantitative research design with cross sectional. The population taken in this study is a teenager (women of fertile age) who experience dysmenorrhea in IMC STIKes Bintaro with 100 sample number of Sorority, the determination of sample with random sampling technique and calculated with the formula slovin obtained results of 56 mahasiswi . The data obtained through the questionnaire has been prepared. In this research analysis test statistic Chi-Square and obtained a value of P = 0.000 < alpha = 0.05 means that H0 is rejected. The conclusions of this study, namely, there is a significant relationship between dysmenorrhea with learning activities at IMC STIKes Bintaro.